Peran dan Fungsi Kelembagaan Mukim dalam Penyelesaian Perselisihan: Analisis Praktek Hukum Adat di Aceh - Muslim Zainuddin (Sharia and Law Faculty, 2017)
Mukim is one of the Acehnese customary institutions in charge of resolving disputes that occur in the community. Within Acehnese customary judicial process, the mukim is positioned at the second level after the gampong. One of the mukim's duties de jure, as stipulated in Article 4 letter (e) of Aceh Qanun No. 4/2003 on Mukim Government, is to provide judicial decisions in the event of customary disputes or cases and customary laws. However, the role of mukim has begun to decrease in terms of resolving community problems. The purpose of this study was to investigate the factors that influenced nonoptimal roles of the mukim, the mechanisms used by the mukim in resolving disputes within the Acehnese society, and the philosophical, juridical and sociological values of the dispute settlements implemented by the institutional mukim. The study used empirical legal method to describe the implementation of the laws on the mukim authority in resolving disputes. The study took place in five areas: Banda Aceh, Aceh Besar, Bireuen, Aceh Tengah, and Nagan Raya. The primary data came from interview and FGDs with Keuchik, Mukim, Police, NGOs, and academicians concerning on Aceh customary laws. The secondary data included primary, secondary, and tertiary legal materials. The primary legal material was the Law regulating the Mukim, the secondary ones came from documentation study including books, journals, and research findings in the library on mukim, and the tertiary ones were from dictionaries and encyclopedias. The results of the study showed that the factors causing nonoptimal roles of the mukim included the human resources, poor training and development, lack of funding, and conflict in Aceh. The customary court at the mukim level had similar ways of resolution as that at the gampong. Likewise, the mechanisms to settle were the same i.e., mutual deliberation and mediation. The difference laid only in the procedural systems. In terms of the philosophical values, both mukim and gampong used the win-win solution principle, creating a harmony between the parties involved, saving time, saving cost, having a moment of connecting kinship between people (silaturahim), and following the teaching of Islam. These findings are hoped to provide insights to people to promote dispute settlement through customary institutions i.e., mukim and gampong prior to taking the cases to the police. It is also hoped that the police will not follow-up the case reports that do not use the customary procedures, and that the executive and legislative institutions can initiate a provincial Qanun which is oriented towards the mukim empowerment proportionally and professionally. Further, socialization on such customary practices should be done at every level of the community in order for the public to be more aware of the mukim’s dispute resolution.